Implementation of the Pieces Method at Levelovo Application User Satisfactiont - Elsa Phelia; Nur Aini; Iwan Setiawan (Yayasan Kita Menulis, 2024)
Technological advances in payment systems replace the role of cash to non-cash forms that are more efficient and economical. One application that has become an alternative choice for many people in making non-cash payment transactions is the OVO application. This research uses the PIECES method which aims to determine the level of satisfaction of OVO application users in Tebat Agung Village based on performance, information, economics, control and security, efficiency and service (service). The results of this research show that the OVO application received an average total score of 3.40, which shows that users are very satisfied with the OVO application in Tebat Agung Village